Formaldehyde Exposure and Mortality Risks From Acute Myeloid Leukemia and Other Lymphohematopoietic Malignancies in the US National Cancer Institute Cohort Study of Workers in Formaldehyde Industries. Issue 7 (July 2015) - Checkoway, Harvey; Dell, Linda D.; Boffetta, Paolo; Gallagher, Alexa E.; Crawford, Lori; Lees, Peter SJ.; Mundt, Kenneth A.
Abstract : Objectives: To evaluate associations between cumulative and peak formaldehyde exposure and mortality from acute myeloid leukemia (AML) and other lymphohematopoietic malignancies. Methods: Cox proportional hazards analyses. Results: Acute myeloid leukemia was unrelated to cumulative exposure. Hodgkin lymphoma relative risk estimates in the highest exposure categories of cumulative and peak exposures were, respectively, 3.76 ( P trend = 0.05) and 5.13 ( P trend = 0.003). There were suggestive associations with peak exposure observed for chronic myeloid leukemia, albeit based on very small numbers. No other lymphohematopoietic malignancy was associated with either chronic or peak exposure. Conclusions: Insofar as there is no prior epidemiologic evidence supporting associations between formaldehyde and either Hodgkin leukemia or chronic myeloid leukemia, any causal interpretations of the observed risk patterns are at most tentative. Findings from this re-analysis do not support the hypothesis that formaldehyde is a cause of AML.